Sirenomelia: The role of post - Mortem diagnostic imaging - A. Russo; A. Reginelli; M. Pignatiello; M. Montella; G. Toni; S. Cappabianca; R. Grassi (Elsevier, 2021)
Background: Sirenomelia, also known as "mermaid syndrome" is a rare lethal condition characterized by a single midline limb, variable lower spinal column defects and visceral abnormalities. We present a case of sirenomelia diagnosed during the 34th week of gestation. Case report: A pregnant 30 years-old woman at 34th week of gestation was referred to the Department of Gynecology and Obstetrics of the Università della Campania "Luigi Vanvitelli" (Italy), with a suspect of intrauterine fetal death; confirmed by Ultrasonography (US) which also detected the presence of severe oligo-hydramnios and complex fetal polymalformations. The mother delivered a death-baby weighing 1.7 kgs. External examination showed a single lower limb, which ended with a malrotated and almost totally fused foot with nine toes. Post-mortem X-ray and Computed Tomography (CT) examinations of the baby revealed the presence of a single midline fibula and a sacro-coccigeal malformation with fusion of the isk bones. Two independent right and left femurs and tibias were present. Conclusion: Sirenomelia is a multisystemic human malformation without explicit etiology and generally not compatible with the normal life. Intrauterine diagnosis of sirenomelia may be difficult in the second or third trimester, because of the concomitant severe oligohydramnios. The early diagnosis of this lethal malformation during suitable gestation week is fundamental to the treatment plan and termination of pregnancy. The use of CT and MRI-virtual autopsy are useful to replace conventional autopsy, and for the evaluation of the malformations of the internal organs, for the prevention of future family pathologies.